Lung Aging and Lung Function Assessment in Elderly - Wesnawa, Made Agustya Darma Putra; Subagiarta, I Made; Nathania, Evelyn (Jurnal Respirasi, 2025)
The lung is one of the organs that experiences the most frequent decline in function among the elderly. Reduced lung function associated with aging is a physiological condition. The lungs transform both their cellular composition and their functional capabilities. The lungs of an aging population may show structural changes to the respiratory muscles, chest wall, lung parenchyma, and upper and lower respiratory tracts. The elderly are more susceptible to reduced lung perfusion, respiratory mechanics, infection, and weaker respiratory muscles because of aging. The body plethysmograph, oscillometer, spirometry, and carbon monoxide (CO) diffusing lung capacity are techniques used to assess lung function in the elderly. For elderly people, lung function testing might be challenging due to frailty and cognitive decline. Consequently, choosing the best lung function test method for the elderly and offering an accurate and suitable interpretation of the test findings are crucial. Early detection of changes in lung function and accurate assessment of lung function can help identify lung function abnormalities in the elderly and give the appropriate treatment and intervention. This review focused on lung aging, the potential benefits and drawbacks of different lung function tests in the elderly, and the proper way to interpret specific lung function tests.